Atmospheric chemistry of ethers, esters, and alcohols on the lifetimes, temperature dependence, and kinetic isotope effect: an example of CF3CX2CX2CX2OX with OX reactions (X = H, D). Issue 42 (14th April 2016) - Bai, Feng-Yang; Wang, Xu; Sun, Yan-Qiu; Wang, Rong-Shun; Pan, Xiu-Mei
Abstract : Mechanisms and kinetics of the reaction of CF3 CX2 CX2 CX2 OX with OX (X= H, D) radical are investigated on a sound theoretical basis. Abstract : The dual-level direct dynamics method is employed to investigate the hydrogen abstraction reaction of CF3 CH2 CH2 CH2 OH (CF3 CD2 CD2 CD2 OD) with OH (OD) radicals. Four possible reaction channels caused by different positions of hydrogen atom attack are found. All the stationary points are studied with the ab initio and density functional theories. Single points computation is further refined by CCSD(T) and QCISD(T) methods combined with the 6-311++G(d, p) basis set in the minimum energy paths (MEP). Rate constants for each reaction channel, obtained by canonical variational transition state (CVT) coupled with the small curvatures tunneling (SCT) correction, are found to coincide with the available data in experiments. Calculations show that the variational effect was small in 200–2000 K, while the tunneling effect is large for every reaction channel in low-temperature regions. It is shown that the H-abstraction from the –CH2 O– group is the primary channel. Standard enthalpies of formation for the species are computed, and the kinetic isotope effects for reactions CF3 CH2 CH2 CH2 OH/CF3 CD2 CD2 CD2 OD + OH and CF3 CH2 CH2 CH2 OH + OH/OD are discussed to provide valuable information for subsequent research. In addition, atmospheric lifetimes of a series of related ethers, esters, and alcohols are estimated. The Arrhenius expression for the title reaction k ( T ) = 3.43 × 10 −21 T 3.22  exp(741.70/ T ) cm 3 per molecule per s is also provided.